Decentralized Renewable Power Generation Using IOT and Blockchain Technology - Kavin, Mr. R.; Jayakumar , Dr. J. (International Journal of Basic and Applied Sciences, 2025)
The increasing demand for clean and reliable energy has driven the adoption of decentralized renewable power generation systems. Integrating Internet of Things (IoT) and blockchain technology can enhance efficiency, transparency, and security in distributed energy networks. IoT enables real-time monitoring and control of renewable energy sources (such as solar, wind, and microgrids), while blockchain ensures tamper-proof energy transactions, peer-to-peer (P2P) energy trading, and automated smart contracts. This study explores a decentralized energy framework where IoT devices collect data on energy production, consumption, and grid stability, while blockchain facilitates trustless energy exchanges among prosumers (producer-consumers). The proposed system eliminates intermediaries, reduces costs, and improves grid resilience by leveraging smart meters, distributed ledgers, and consensus algorithms. The future scope of power generation is based on Decentralized power generation depends on Renewable energy sources (solar, wind). By using decentralized power generation, we can be able to achieve bidirectional power flow, one can able to transmission as well as receiving electrical power. This new concept introduces blockchain technology in Distributed Generation for monitoring and recording energy transactions between two peers. These Peer-to-Peer energy transactions are done in the DC Microgrid using blockchain Technology with smart contracts for energy trading.